PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL DAN MENENGAH (SAK EMKM) DALAM PENYUSUNAN LAPORAN KEUANGAN KEDAI LALIE DJIWO DI KOTA PASURUAN - Mochammad Hafid Rusli Afiffudin; Achmad Maqsudi (Gapenas Publisher, 2023)
The purpose of this study is to analyze how the Indonesian Financial Accounting Standards for Micro, Small, and Medium-sized Entities (SAK EMKM) are applied in the preparation of financial statements for Kedai Lalie Djiwo. The research methodology employed in this study is qualitative-descriptive with the aim of providing a detailed explanation of the implementation of SAK EMKM in the financial reporting of Kedai Lalie Djiwo in Pasuruan City. Kedai Lalie Djiwo is a company engaged in the goods and services sector (culinary, guesthouse, and travel agency), focusing on the development of natural tourism and demonstrating a well-integrated organizational structure, as well as a strong commitment to local potential development and community empowerment. The findings of this research indicate limitations in understanding financial statements, although the respondents have limited knowledge regarding the objectives and benefits of financial reporting